03 Standing Postural Control in the Older Adult using Proposed Virtual Light Touch Contact System. (20th December 2019) - Shimatani, Koji; Sakata, Mami; Mitani, Ryoma; Shima, Keisuke
Abstract: Background: We proposed a novel standing-function evaluation system based on Virtual Light Touch Contact (VLTC). In this approach, virtual partition with virtual inertia, viscosity, stiffness is set around the subject. When the subject touches the virtual partition, virtual force is estimated. And virtual force is feed backed to fingertip in the form of vibrotactile stimulation. Random on/off control of virtual forces from the virtual partition enabled evaluation of standing function based on the presence or absence of somatic sensory stimulation to the fingers. Purpose: The purpose of this study was to investigate the adults' postural control during quiet standing using our VLTC system. Method: The participants were 60 adults (72.7±7.6 y/o). We used our proposed vibrotactile stimulation device and a Kinect 2 sensor (Microsoft) and a Wii Balance Board (Nintendo) are utilized to determine the centre of pressure (COP). We measured quiet standing with closed eyes and legs using a VLTC system. We compered body sway using total sway length (TSL), rectangular area (RA), average velocity (AVel), and average vector (AVec) of COP in each of the 60's, (22 participants) 70's (28 participants), 80's (10 participants). Results: The TSL and AVel in the 60's was significantly smaller than that in the 80's (p<0.05). And the TLS and AVel in the 70's tended to be smaller than that in the 80's (p=0.07). The other parameters were non-significant. Conclusion: We showed that body sway increased when the old adults were quiet standing with VLTC system. Stability of the human posture by LTC is due to an increased amount of feedback, especially from the somatosensory system, among the system required for postural adjustment. Authors assume that the old adults could not depend on VTC system due to the decreased in fingertip somatosensory function, and the old adult's body sway was increased.